2018
DOI: 10.1111/dme.13768
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in coronary plaque composition evaluated by coronary computed tomography angiography in newly diagnosed Type 2 diabetes: association with low‐grade inflammation

Abstract: In people with newly diagnosed Type 2 diabetes, women had lower absolute coronary plaque volumes but a more unfavourable plaque composition and enhanced systemic inflammation compared with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Women with diabetes might be in a more pro-thrombotic state than men, which may lead to lacunes and atrophy, and a more general decline in brain health, even when the prevalence of diabetes is similar in both sexes (Smith et al, 2012 ; Neergaard-Petersen et al, 2014 ). They generally also have greater levels of systemic inflammation and more oxidative stress than men with diabetes, leading to impaired vascular reactivity, which is specifically associated with the occurrence of lacunes (Mrgan et al, 2018 ). Sex-dependent differences in vascular physiology may therefore render women more susceptible to the cerebrovascular complications of diabetes, and also lead to functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…Women with diabetes might be in a more pro-thrombotic state than men, which may lead to lacunes and atrophy, and a more general decline in brain health, even when the prevalence of diabetes is similar in both sexes (Smith et al, 2012 ; Neergaard-Petersen et al, 2014 ). They generally also have greater levels of systemic inflammation and more oxidative stress than men with diabetes, leading to impaired vascular reactivity, which is specifically associated with the occurrence of lacunes (Mrgan et al, 2018 ). Sex-dependent differences in vascular physiology may therefore render women more susceptible to the cerebrovascular complications of diabetes, and also lead to functional decline.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 44 In diabetic patients, women may have lower plaque volumes but enhanced systemic inflammation, which may cause the increased risk of developing plaques and worse plaque composition. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Observational studies also demonstrated that women with diabetes had higher risk of CVD than male patients 32,44 . In diabetic patients, women may have lower plaque volumes but enhanced systemic inflammation, which may cause the increased risk of developing plaques and worse plaque composition 45 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the global decline in mortality and incidence of CVD over the last decades, seen both in subjects with and without diabetes, the latter still experience a 2–3 times higher risk as compared to non-diabetic matched controls [13]. This higher risk, combined with the high prevalence of subjects that already have cardiovascular complications at the time of diabetes diagnosis [46], makes the screening for chronic complications highly recommended for all patients with type 2 diabetes (T2D). Early identification of complications can result in the prescription of more aggressive treatment regimen that have the potential to slow their natural progression.…”
Section: Introductionmentioning
confidence: 99%